Materi Qawaid Metode Tamyiz 1 dalam Konsep Pembaharuan Nahwu Syauqi Dhayf - Afyuddin, Moh Sholeh; Imamah, Ayunda; Munawwir, Ahmad; Irhas, Moh (Prodi Pendidikan Bahasa Arab FTK UIN Sunan Ampel, 2023)
Purpose- This research aimed to create a scientific dialogue between the Tamyiz Method - as a fast method for learning Arabic Qawaid - and the Nahwu renewal concept initiated by Syauqi Dhayf. Design/Methodology/Approach- This research used qualitative methods with the type of library research. Data collection was by collecting and reading library materials related to the research theme, making notes, and analyzing them deductively using Miles and Haberman's analysis stages. Findings- The results of this research stated that the Tamyiz 1 material could apply the six principles of Nahwu Syauqi Dhayf renewal except for “the elimination of i'rob taqdiri or mahalli analysis”, because the learning material in Tamyiz 1 – which aimed to be smart tarjamah of the Quran – did not introduce i'rob analysis. The rest principles – such as reformulation, reorientation, redefinition, deleting additional materials that do not lead to achieve learning objectives, and adding material considered significant in achieving learning objectives – could be seen in several structures of Tamyiz 1 materials, such as the addition of the mujarrod chapter to find the original letter of a sentence, focuses the material on identifying harf, fiil and isim with its characteristics and patterns (wazan) which have a high frequency of appearance in the QS. Al-Baqarah. Several other chapters known in the classical nahwu standards are not taught because the materials are focused and arranged concisely to achieving Tamyiz 1 learning objectives. Research Implications- The results of this research have implications for The results of this research have implications for learning qawaid with the 'fast method' which has been developed by many Arabic language scholars, including the Tamyiz Method. The results of this research can provide an epistemological explanation regarding fast Nahwu learning methods.